ANALISIS PENGELOLAAN LABORATORIUM ILMU PENGETAHUAN ALAM (IPA) SMP NEGERI 1 PURWANTORO - Nurhamudin, Nurhamudin (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
The aim of this research is to describe the management of the science laboratory which includes (1) planning (2) organizing (3) implementation (4) monitoring and evaluation at SMPN 1 Purwantoro. The approach used in this research is a qualitative approach with a case study type of research because science laboratory management is a unified system. The data collection methods used were observation, documentation, questionnaires given to students in grades VII, VIII, and IX, totaling 96 students, as well as interviews conducted with the school principal, deputy head of facilities and infrastructure, laboratory head, and science teacher. The research results show the following. (1) planning for the science laboratory work program has not been implemented properly; (2) the organization carried out is still not in accordance with laboratory management regulations; (3) the implementation of the science laboratory work program is still not running intensively; (4) monitoring and evaluation is carried out internally; (5) factors that influence the management of the science laboratory at SMPN 1 Purwantoro, namely laboratory assistants, students, time, and limited equipment and materials